Injured trigeminal nerve in maxillofacial nonneoplastic deseases - Tymofeiev, О. О.; Vesova, О. П. (Actual Dentistry, 2020)
Purpose: to study the frequency and reasons for injures II branch of trigeminal nerve complications after surgical phase of dental implantation on maxilla. Patients and methods. Under our supervision there were 1096 patients with secondary nevrogenic defeats of peripheral branches of trigeminal nerve, which were examined and treated in Clinic of Maxillofacial Surgery at Shupyk National Medical Academy of Postgraduate Education. Results. Clinical improvement and liquidation of painful symptomatology correlated with normalization of electrophysiological data of condition defeated peripheral branches of trigeminal nerve. Conclusions. Recommended method reduces term of treatment for neuralgia, neuralgo-neuritis, neuritis of II branch of trigeminal nerve more than 2,5 times.